Trends in prevalence and correlates of intimate partner violence against women in Zimbabwe, 2005-2015 - Jeanette Iman'ishimwe Mukamana; Pamela Machakanja; Nicholas Kofi Adjei (BMC, 2020)
Abstract Background Intimate partner violence (IPV) is a widespread problem affecting all cultures and socioeconomic groups. This study explored the trends in prevalence and risk factors associated with IPV among Zimbabwean women of reproductive age (15-49 years) from 2005 to 2015. Methods Data from the 2005/2006, 2010/2011 and 2015 Zimbabwe Demographic and Health Survey (ZDHS) on 13,409 women (survey year: 2005/2006; n = 4081), (survey year: 2010/2011; n = 4411) and (survey year: 2015; n = 4917) were analyzed. Multiple logistic regressions and hierarchical modelling techniques were applied to examine the associations between demographic characteristics, socioeconomic status, media exposure and IPV against women. We further estimated IPV prevalence by type (physical, sexual and emotional) over time. Results The prevalence of IPV decreased from 45.2% in 2005 to 40.9% in 2010, and then increased to 43.1% in 2015. Some of the risk factors associated with IPV were younger age, low economic status, cohabitation and rural residence. Educational attainment of women was however not significantly associated with IPV. Conclusions The findings indicate that women of reproductive age are at high and increasing risk of physical and emotional violence. There is thus an urgent need for an integrated policy approach to address the rise of IPV related physical and emotional violence against women in Zimbabwe.